Amyotrophic lateral sclerosis versus multifocal motor neuropathy: utility of MR neurography - Kronlage, Moritz; Knop, Karl Christian; Schwarz, Daniel; Godel, Tim; Heiland, Sabine; Bendszus, Martin; Bäumer, Philipp (Radiology, 2019)
Purpose: To assess diagnostic accuracy of MR neurography in the differential diagnosis of ALS and MMN. Materials and Methods: This prospective study was conducted between December 2015 and April 2017. Study participants with ALS or MMN underwent MR neurography of the lumbosacral plexus, midthigh, proximal calf, and midupper arm of the clinically more affected side using high-resolution T2-weighted sequences. Matched healthy study participants who underwent MR neurography served as a control group. Two blinded readers independently rated fascicular lesions and muscle denervation signs on a five-point scale and made an image-only diagnosis, which was compared with the clinical diagnosis to assess diagnostic accuracy (reported for ALS vs non-ALS and MMN vs non-MMN). The Kruskal-Wallis test was used to compare readers’ scoring results. Results: Twenty-two participants with ALS (12 men and 10 women; mean age 6 standard deviation, 62.3 years 6 9.0), eight participants with MMN (seven men and one woman; mean age, 57.6 years 6 18.6), and 15 healthy participants (seven men and eight women; mean age, 59.1 years 6 10.9) were enrolled in this study. Nerves of participants with ALS either appeared normal or showed T2-weighted hyperintensities without fascicular enlargement (reader 1, 22 of 22 participants; reader 2, 21 of 22 participants). In contrast, nerves in MMN were characterized by fascicular swellings (reader 1, six of eight participants; reader 2, seven of eight participants). Muscle denervation signs were more prominent in ALS than in MMN. Inter-rater reliability for blinded diagnosis was k of 0.82. By consensus, the sensitivity to diagnose ALS (vs MMN and healthy control participants) was 19 of 22 (86% [95% confidence interval CI: 67%, 95%]). The corresponding specificity was 23 of 23 (100% [95% CI: 86%, 100%]). The sensitivity to diagnose MMN (vs ALS and healthy control participants) was seven of eight (88% [95% CI: 53%, 99%]). The corresponding specificity was 37 of 37 (100% [95% CI: 91%, 100%]). Conclusion: MR neurography is an accurate method for assisting in the differential diagnosis of amyotrophic lateral sclerosis and multifocal motor neuropathy.
Gesehen am 15.10.2019